Multicultural Curriculum as a Strategy for Strengthening Intercultural Literacy in Responding to Global Challenges: - R. Madhakomala; Lutfia Syafrudin; Abdullah, Sultan Fadhly (Green Publisher, 2025)
Globalization demands an education system that is adaptive to diversity and socio-cultural challenges. Multicultural curriculum is an important strategy in strengthening intercultural literacy and forming tolerant characters in a pluralistic society. This article analyzes the role of multicultural curriculum in responding to global challenges through a literature review of national and international scientific journals (2020-2025). The results show that the integration of multicultural values in the curriculum can improve cross-cultural understanding, tolerance, and students' readiness to face the global era. However, its implementation still faces obstacles such as the dominance of majority values, limited teacher competence, and policies that are not fully inclusive. Systematic policies and strategies are needed to ensure equitable and diversity-responsive education.